Long-Term Outcomes After Linac Radiosurgery for Benign Meningiomas. Issue 7 (July 2020) - Pou, P.; Biau, J.; Verrelle, P.; Lemaire, J.J.; El Ouadih, Y.; Chassin, V.; Magnier, F.; Dedieu, V.; Lapeyre, M.; Dupic, G.; Khalil, T.
Abstract: Aims: Although several studies on outcomes following stereotactic radiosurgery (SRS) for benign meningiomas have been reported, Linac-based SRS outcomes have not been as widely evaluated. The aim of this retrospective institutional single-centre study was to determine long-term outcomes of Linac-based SRS for benign intracranial meningiomas. Materials and methods: From July 1996 to May 2011, 60 patients with 69 benign meningiomas were included. All patients were treated with single-fraction Linac-based SRS with four to five non-coplanar arcs, dynamic or not. The marginal dose prescribed for the periphery was 16 Gy. Prognostic factors associated with local control, progression-free survival (PFS) and overall survival were tested. Results: The median follow-up was 128 months. No patient was lost to follow-up. The values observed at 1, 5 and 10 years were, respectively, 100%, 98.4% and 92.6% for local control, 94.9%, 93.2% and 78% for PFS and 100%, 94.7% and 92.7% for overall survival. In univariate analysis, local control after SRS was significantly higher for skull base and parasagittal meningiomas compared with convexity meningiomas ( P = 0.031). Multivariate analyses showed significantly longer PFS when the minimum dose delivered to the tumour was greater than 10 Gy ( P = 0.0082). No grade 5 toxicity was reported. Conclusion: Our long-term results from a large sample size of benign meningiomas treated with Linac-based SRS confirmed excellent local control (>90%) and good safety, which is in line with published studies on Gamma Knife surgery. Above all, we showed significantly poorer PFS if the minimum dose to the tumour was under 10 Gy. Highlights: Linac-based stereotactic radiosurgery for benign meningiomas provides excellent 10-year local control >90%. Only 9% adverse effects were observed, 2% of which were permanent and 7% transient. Convexity meningiomas exhibited significantly poorer local control. Progression-free survival was significantly shorter if the minimum dose was <10 Gy.